Islamic Law and Social Sciences: A Bibliometric Analysis of Global Scholarly Trends (2012–2025) - Fikri, Mursyid; Indriana, Indriana (Westscience Press, 2025)
This study aims to map the development of scientific literature on Islamic law through a bibliographic review approach to 201 articles published between 2012 and 2025. All articles were categorized as final stage articles, written in English, and analyzed in the context of the social sciences (Subject Area: Social Sciences). The focus of the study was on key topics such as Islamic Law, Fiqh, Islamic Jurisprudence, Sharia, Islamic Finance, Maslahah, Maqasid al-Shari'ah, and Shariʿah Compliance. Bibliographic data were obtained from indexed scientific literature and cleaned using OpenRefine software to ensure consistency of information related to titles, authors, affiliations, and keywords. The articles were published in 84 different scholarly journals, all of which were categorized as Open Access, either Gold or Hybrid Open Access, demonstrating the open access to Islamic legal knowledge globally. The analysis showed that the publications came from authors with affiliations spread across different countries, with a total of more than 20 countries. The three countries with the highest contributions to the literature are Indonesia (91 publications), Malaysia (26 publications), and Turkey (14 publications). This indicates the academic dominance of the Southeast Asian and West Asian regions in contemporary Islamic law discourse. The results of the analysis also show that the themes of Islamic Law and Fiqh are the most dominant in the titles of publications, while topics such as Maqasid al-Shari'ah and Shariʿah Compliance, although not yet prominent in frequency, show significant potential in the development of applied studies, especially in the fields of Islamic finance and contemporary legal policy. This study contributes to the mapping of academic trends in Islamic law and identifies publication gaps that can serve as a basis for further research based on a bibliometric approach.